2020
DOI: 10.1007/s10882-020-09746-w
|View full text |Cite
|
Sign up to set email alerts
|

Inferencing Abilities of Deaf College Students: Foundations and Implications for Metaphor Comprehension and Theory of Mind

Abstract: Understanding nonliteral language requires inferencing ability and is an important but complex aspect of social interaction, involving cognitive (e.g., theory of mind, executive function) as well as language skill, areas in which many deaf individuals struggle. This study examined comprehension of metaphor and sarcasm, assessing the contributions of hearing status, inferencing ability, executive function (verbal short-term/working memory capacity), and deaf individuals' communication skills (spoken versus sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The results showed that these individuals scored significantly lower on all three ToM tests than their hearing peers. The same results were found in Edwards et al (2021) , where deaf college students performed worse than their hearing peers on sarcasm, metaphor comprehension tasks, and reasoning tasks.…”
Section: Introductionsupporting
confidence: 77%
“…The results showed that these individuals scored significantly lower on all three ToM tests than their hearing peers. The same results were found in Edwards et al (2021) , where deaf college students performed worse than their hearing peers on sarcasm, metaphor comprehension tasks, and reasoning tasks.…”
Section: Introductionsupporting
confidence: 77%
“… 46 , 47 This shift in information acquisition has increased their cognitive load. 6 Additionally, executive functioning, a cognitive domain affected by auditory deprivation, further limits their ability to process complex information and make decisions. 48 When faced with heavy academic pressure, social challenges, or uncertainty about the future, college students with hearing loss may feel overwhelmed, resulting in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Research has shown that college students with hearing impairments often exhibit significant deficits in working memory, including verbal memory span and verbal working memory capacity, which are related to executive function. 6 These students often struggle with understanding verbal instructions, processing information, and mastering social norms when completing tasks and making plans. Similar to their normal-hearing peers, hearing-impaired college students are at a critical stage in their lives, facing various academic, professional, and social challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation was the use of a metaphor artifact, which caused some difficulties for participants to understand what was being asked as examples. In a recent study, Edwards et al (2021)) compared metaphor comprehension among deaf and hearing students, reporting a better understanding of nonliteral language among hearing participants. Based on that, further reflection on the continuity of using this approach should be weighted.…”
Section: Categorymentioning
confidence: 99%